HIV/AIDS in Tanzania: History, national response, and challenges - Lekey-Kawo, Ndenengo-Grace; Adamu, VE (Orapuh Journal, 2023)
Tanzania, alongside 34 other countries, accounts for more than 90% of the people acquiring new HIV infections globally. Since the beginning of the HIV/AIDS epidemic, the country has put forward a response that is intended to reduce its incidence and improve quality of life for sufferers. The country has also now keyed into the UNAIDS 90-90-90 fast-track targets to achieve the global target of ending HIV/AIDS as a public health threat by 2030. This review aimed to discuss HIV/AIDS in Tanzania, detailing the historical events, the national response, the challenges in addressing the epidemic, and the factors related to national response sustainability. We searched valid academic sources for information on the areas covered by our study scope and found some strategic literature, which we reviewed. The first HIV/AIDS patients in Tanzania were seen in October 1983 at Bukoba Regional Hospital in the Kagera Region, located in the North-Western part of the country. To combat the HIV/AIDS menace, Tanzania evolved a national response to the scourge to protect the public’s health. The governance of the HIV/AIDS national response system is vested in the division of National Response in the Tanzania Commission for AIDS (TACAIDS). This formation co-ordinates the multi-sectoral implementation of HIV/AIDS interventions in the country. The sectoral response is co-ordinated through the public and private sectors, civil society organisations, regions, local government authorities, and the community. Tanzania has adopted the WHO 2015 guidelines for treating all people living with HIV (PLHIV) irrespective of disease stage. However, the Tanzanian national response to the HIV/AIDS scourge in the country is fraught with challenges that border on certain cultural, societal, structural, and political realities and value systems. Surmounting these challenges would require concerted efforts of relevant stakeholders directed at the root causes, especially the challenges that concern financing and the health workforce. Thus, sustainability will depend on continued political leadership and adequate funding.